Understanding the transdiagnostic mechanisms underlying emerging psychopathology in adolescence: study protocol of a 1-year prospective epidemiological (EMERGE) study - Xenia Anna Häfeli; Anja Hirsig; Stefanie J Schmidt (BMJ Open)
Introduction Adolescent mental health is a global public health challenge as most cases remain undetected and untreated, and consequently, have a high likelihood of persistence or recurrence. It is critical to improve early detection of mental disorders and to target individuals experiencing subclinical symptoms. However, most indicated prevention approaches have been developed for risk syndromes of specific mental disorders. This contradicts the increasing recognition of emerging psychopathology as a complex system characterised by rapid shifts in subclinical symptoms, cutting across diagnostic categories and interacting with each other over time. Therefore, this study aims to examine the dynamic course, pattern and network of subclinical symptoms and transdiagnostic mechanisms over time.Method and analysis The EMERGE-study is a prospective, naturalistic, 1-year follow-up study. A general population sample of 1196 adolescents will be recruited. Inclusion criteria are age between 11 and 17 years, German language skills, main residency in Switzerland and access to internet. Individuals will be excluded if they have a current or lifetime axis I mental disorder. Assessments of subclinical symptoms of several mental disorders and potential transdiagnostic mechanisms will be conducted at baseline and at 3-month, 6-month, 9-month and 12-month follow-up. Structural equation modelling will be used to estimate the homotypic and heterotypic patterns of subclinical symptoms and the associations with transdiagnostic mechanisms. Latent growth mixture modelling and growth mixture survival analysis will be carried out to identify subclasses of individuals with different trajectories of subclinical symptoms that may be predictive of an onset of a mental disorder. Network analysis will be applied to assess the centrality of subclinical symptoms and how networks of emerging psychopathology change over time.Ethics and dissemination Ethical approval was obtained from the Bern Cantonal Ethics Committee (ID 2020-02108). All findings will be disseminated by publication in peer-reviewed scientific journals and by presentation of the results to conferences and stakeholder organisation events.